Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I know how to solve an exact equation like

$$M(x,y) + N(x,y)y=0 $$

We just check $$\frac{\partial M}{\partial y} =\frac{\partial N}{\partial x} $$

If so, then it's just a little bit of algebra, taking anti-derivative and solve, such that $f = f(x,y) = c$, where we can obtain $f$ by just taking integal w.r.t. $x$ etc.

But now I'm stuck with integrating factors. I can do it if the integrating factor $\mu=\mu(x)$ depends only on one variable. But now I want to do another exercise, which uses a function of the form $\mu(x+y)$.

How can I solve $$(7x^3+3x^2y+4y) +(4x^3+x+5y)y'=0 $$ I'm given a hint that I should use a function of the form $\mu(x+y)$.

I guess I should just multiply by $(x+y)^m$ for an arbitrary $m$, but I don't know how to do the algebra after I multiplied...

I guess something like this :

$$\frac{\partial (M \mu)}{\partial y}= m(x+y)^{m-1}(7x^3+3x^2y+4y) + (x+y)^m(3x^2+4) =$$

$$\frac{\partial (N\mu)}{\partial x} = m(x+y)^{m-1}(4x^3+x+5y) + (x+y)^m(12x^2+1) $$

How solve for $\mu$ ?

share|cite|improve this question
your integrating factor doesn't need to be of the form $(x+y)^m$. It could also be something like $e^{(x+y)^2}$ or something like that. – Slugger Jan 26 '13 at 14:43
You are doing the same course ? ;-). Thanks, I didn't realize that – Applied mathematician Jan 26 '13 at 14:44
How about changing to $w=x+y$ and writing the equation in terms of $x,w$. Now $\mu=\mu(w)$. – Maesumi Jan 26 '13 at 15:00
up vote 3 down vote accepted

Hint: Let you have an OE like $$M(x,y)dx+N(x,y)dy=0$$ and let $\mu=\mu(z(x,y))$ be an integrating factor for it. If $$\frac{M_y-N_x}{Nz_x-Mz_y}$$ be a function respect to $z$ then $$\mu=\exp\left(\int\frac{M_y-N_x}{Nz_x-Mz_y}dz\right)$$. Here $z=x+y$, so $z_x=1,z_y=1$ and therefore your integrating factor is $\mu=\exp\left(\int\frac{M_y-N_x}{N-M}dz\right)$. You can easily find $\mu$ by doing $$(\mu M)_y=(\mu N)_x$$ as well. For thsi problem $$\mu=\exp\left(\int\frac{3x^2+4-12x^2-1}{4x^3+x+5y-7x^3-3x^2y-4y}dz\right)=\exp\left(\int\frac{3(1-3x^2)}{(x+y)(1-3x^2)}dz\right)$$ which if $3x^2-1\neq0$ then $$\mu=\exp\left(\int\frac{3}{x+y}dz\right)=\exp\left(\int\frac{3}{z}dz\right)$$ I think you can do the rest.

share|cite|improve this answer

Your integrating factor is $$ \mu(x+y)=(x+y)^3. $$

To find it you use the usual strategy expressing $$ \mu_yM-\mu_xN=\mu(N_x-M_y).\tag{1} $$ After some simplification you can find that $$ \frac{N_x-M_y}{M-N}=\frac{3}{x+y}. $$ Hence, if $\mu(x,y)=\mu(x+y)$ $(1)$ simplifies to $$ \mu'_w=\frac{3\mu}{w},\quad w=x+y, $$ from which you find your integrating factor.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.